OPTIMIZING ANTIBIOTIC USE IN PEDIATRIC ACUTE GASTROENTERITIS: A QUALITY IMPROVEMENT STUDY USING THE FOCUS-PDCA FRAMEWORK - Fawzyh J Alkhadidi; Bassam Alzaidi; Nasser Alharthi; Najmah Alotaibi; Rehab Altalhi; Ahmed Almalki; Sultan almoammri; Elshorbagy, Hatem (Universitas Airlangga, 2026)
Background: Acute gastroenteritis is a leading cause of pediatric healthcare utilization and is predominantly viral; however, inappropriate antibiotic use remains common, contributing to antimicrobial resistance, adverse events, and increased healthcare costs. This study aimed to reduce inappropriate antibiotic prescribing through a structured quality improvement intervention. Methods: A quasi-experimental pre–post quality improvement study without a control group was conducted over six months. A total of N pediatric patients with acute gastroenteritis were included based on predefined inclusion and exclusion criteria. A multifaceted intervention was implemented, including development of evidence-based antibiotic guidelines, optimization of electronic prescribing systems, clinician education, audit and feedback, and caregiver education. Data were collected across iterative improvement cycles. Statistical analysis included chi-square testing and comparison of means, with significance set at p < 0.05. Results: Inappropriate antibiotic use decreased from 40% to 10%, representing a relative risk reduction of 75% (risk ratio 0.25; 95% confidence interval: 0.15–0.42; p < 0.001). Documentation of clinical justification improved from 60% to 90% (p < 0.001), and mean length of stay decreased significantly. No increase in readmission or complication rates was observed. Conclusion: A structured, multifaceted intervention effectively reduced inappropriate antibiotic use while maintaining patient safety. Despite limitations related to study design, the findings highlight the potential for scalable, system-level strategies to enhance antimicrobial stewardship and optimize pediatric healthcare delivery.